Improvement of the cyclone separator performance by the wedge-shaped roof: A multi-objective optimization study. (15th March 2023) - Li, Wansong; Huang, Zhiqiang; Li, Gang
Highlights: The structure of the cylinder roof of the cyclone separator has a significant impact on the separation performance of the cyclone separator. The height and top diameter of the wedge-shaped roof are the main influencing factors. The multi-objective optimization obtains the optimal cyclone separator structure under different inlet velocity. Abstract: The structure of the cyclone separator directly affects the separation performance of the cyclone separator, but there are few studies on the cylinder roof of the cyclone separator. This paper aims to optimize the wedge-shaped roof geometry via numerical simulations. The influence of structural dimensions (the height, the top diameter, and the bottom diameter) of the wedge-shaped roof on the cyclone separator is studied, and the design variables are determined. The sample points are obtained by sampling design variables (the height, the top diameter, and the inlet velocity) using Latin hypercube sampling (LHS). The prediction models of objective variables (the collection efficiency and the pressure drop) are obtained by the response surface methodology. The multi-objective optimization is carried out using the genetic algorithm, and the Pareto solutions are obtained. The results show that the optimal design of the wedge-shaped roof can achieve better separation performance. The optimal structure selected in this paper improves the collection efficiency by 4.2%, and the pressure drop increases by 11%.